Surveying Community Environmental Justice: Urban Runoff Patterns in Eastern Tijuana, México - Carolina Prado; Guillermo Douglass-Jaimes; Colectivo Salud y Justicia Ambiental (Social Sciences)
In an urban region of eastern Tijuana, there are long-standing water runoff sites which community members have identified as having an impact on residents, including contributing to flooding. This community-based participatory research (CBPR) project in collaboration with the Colectivo Salud y Justicia Ambiental (CSJA) used the geospatial surveying tool Survey 123 to conduct community-based monitoring of five runoff sites. Results from 170 completed surveys showed that water runoff was present at these sites on forty-five percent of the days surveyed, although there was no significant relationship between the temporal factors studied and the water quality characteristics surveyed. These findings contribute to the field of border environmental justice by focusing on the understudied issues of runoff and urban flooding as environmental exposures that some communities experience disproportionately. Moreover, while there was a significant relationship between water runoff volume and precipitation events at the water runoff sites, there were sixty-five surveys collected that showed water present when there had been no precipitation event at the site. This finding supports the CSJA members’ assertions that the runoff experienced in the study area is not always connected to precipitation events or pluvial flooding. This project’s results contribute to policy advocacy by countering the policy narrative that this issue is simply a stormwater issue, and by identifying the specific runoff sites to be prioritized in this region.